Seismogenic sources in the Lower Tagus Area using geophysical data - Pinto, Carlos C. (2012)
The Lisbon and Lower Tagus Valley area have suffered the effect of historical earthquakes that caused important damages and loss of lives. Some of these earthquake sources are local but they are still poorly known due to the difficulty in finding geological outcrops, together with low-slip rates and erosion/sedimentation processes that erase surface ruptures. Identification of seismogenic sources capable of producing large earthquakes from low magnitude instrumental seismicity has also proved unreliable in other areas of the world. Therefore, for a proper assessment of seismogenic sources for seismic hazard purposes we have used recently reprocessed and reinterpreted seismic reflection, potential-field data and overlaid relocated epicentres. Here we present a revised structural interpretation of the area based on seismic data and a basement map produced by magnetic modelling, 2D Euler deconvolution and trend analysis. This basement map, which greatly enlarges the seismic coverage of the study area, has shown new insights into deep-seated structures of the Lower Tagus Valley area and their relationship with seismicity. The information from fault parameters collected in this work will also help to locate the sources of historical events such as the 1909 Benavente earthquake using finite-element strong-motion simulation and comparison with observed seismic intensities